Capture area of discrete stochastic non-power servo measuring parameters of radio - Шматок, С.О.; Шматок, О.С. (Proceedings of National Aviation University, 2008)
Areas of capture of discrete stochastic tracing instruments for measuring the non-energetic parameters of radio signals. In this paper, the areas of capture of a first-order discrete stochastic tracking measuring instrument depending on the intensity of external random excitations are calculated on the basis of the difference area method.